2018
DOI: 10.1155/2018/4606053
|View full text |Cite|
|
Sign up to set email alerts
|

ECG Markers of Hemodynamic Improvement in Patients with Pulmonary Hypertension

Abstract: Introduction Several diagnostic tests have been recommended for risk assessment in pulmonary hypertension (PH), but the role of electrocardiography (ECG) in monitoring of PH patients has not been yet established. Therefore the aim of the study was to evaluate which ECG patterns characteristic for pulmonary hypertension can predict hemodynamic improvement in patients treated with targeted therapies. Methods Consecutive patients with pulmonary arterial hypertension (PAH) or chronic thromboembolic pulmonary hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 39 publications
0
24
1
Order By: Relevance
“…Several previous studies, for example, by Waligóra et al and Cheng et al, demonstrated the importance of the P‐wave amplitude, when compared to the other ECG parameters, in revealing hemodynamic improvement in patients with PAH, following the application of targeted pharmacotherapy (Cheng et al, 2017; Waligora, Tyrka, Podolec, & Kopec, 2018). The study by Cheng et al showed a significant correlation between the P‐wave amplitude and the mPAP value ( r = .35, p < .001), and between the P‐wave amplitude and CI ( r = −.22, p = .002).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies, for example, by Waligóra et al and Cheng et al, demonstrated the importance of the P‐wave amplitude, when compared to the other ECG parameters, in revealing hemodynamic improvement in patients with PAH, following the application of targeted pharmacotherapy (Cheng et al, 2017; Waligora, Tyrka, Podolec, & Kopec, 2018). The study by Cheng et al showed a significant correlation between the P‐wave amplitude and the mPAP value ( r = .35, p < .001), and between the P‐wave amplitude and CI ( r = −.22, p = .002).…”
Section: Discussionmentioning
confidence: 99%
“…In adults with PAH, increased P wave amplitude in lead II, the presence of a qR-pattern or increased R wave amplitude in lead V1 are associated with worse hemodynamics and decreased survival (45,46). Treatment-induced changes of ECG parameters reflecting RV hypertrophy are associated with concurrent changes in hemodynamics and survival (47)(48)(49), providing clues that ECG biomarkers can serve as adjunct prognosticators for risk stratification and for monitoring the disease over time.…”
Section: Electrocardiographic Biomarkersmentioning
confidence: 99%
“…In addition, ST segment depression [ 25 ] and higher QRS amplitude also exhibited the information of hypertension [ 26 ]. Meanwhile, the ECG can be potentially used for pulmonary hypertension evaluation [ 27 , 28 ]. Recently, a single ECG signal has been utilized to investigate the hypertension system [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%